INVESTIGATING EFL LECTURERS’ ATTITUDES TOWARDS YOUTUBE AS A TOOL FOR EXTENSIVE LISTENING - Alvina Salsabiela; Sri Setyarini; Muhammad Handi Gunawan (Indonesian EFL Journal, 2024)
Abstract: In Indonesia, teaching English, especially listening, is barely knowledgeable to be taught in teaching-learning activities. Furthermore, some obstacles come along with teachers’ competencies on how to conduct listening skills in teaching-learning activities to support the obstacles solved. YouTube is a knowledgeable tool and one of the motivating and collaborative learning resources that can promote extensive listening activities. Lecturers can utilize it since extensive listening provides an engaging listening practice in line with the usage of YouTube. The article aims to investigate the EFL lecturers' attitudes towards using YouTube as a tool for extensive listening. Open-ended questionnaires and semi-structured interviews collect the leading information to grasp the lecturers' experience during the course implementation. Two of three lecturers were selected to be interviewed for further information from the answers to the open-ended questionnaire. The study employs thematic analysis with supporting Nvivo 12 to organize the data. The findings revealed that lecturers have positive opinions about using YouTube as a tool for extensive listening. The lecturers admitted that implementing YouTube as extensive listening promotes the enjoyment and exposure input by students for lecturers, amounts of learning materials used, accessibility of learning materials is effortless, and high motivation about teaching listening.Keywords: YouTube; extensive listening; lecturers; attitude